New concepts of force measurement systems for specific machining processes in aeronautic industry. (May 2015) - Klocke, F.; Adams, O.; Auerbach, T.; Gierlings, S.; Kamps, S.; Rekers, S.; Veselovac, D.; Eckstein, M.; Kirchheim, A.; Blattner, M.; Thiel, R.; Kohler, D.
Abstract: Precise force measurements are often used for the development of machining processes. A key measure thereby is the specific cutting force, which comprises several factors such as cutting and work piece material as well as the cutting edge geometry. Therefore, it is vital for cutting tests to be as close to the real application as possible in order to guarantee a good alignment and transferability of the results. In many cutting tests carried out in a laboratory environment this cannot sufficiently be ensured. This paper presents two specific processes being applied in aeronautic industry for which force measurement systems were specially developed to satisfy the mentioned requirements. On the one hand, a 4-Component-High-Speed Rotating-Cutting-Force-Dynometer is employed for machining Aluminum parts on a machining center. On the other hand, a specially designed 3-Component Cutting-Force-Dynamometer was installed to an industrial broaching machine tool manufacturing slots in a nickel-based alloy. Besides an introduction of the new equipment, cutting tests being carried out with the piezo-electric sensor technology are analyzed and discussed regarding the achieved results.